Quantification of fairness bias in relation to decisions using a relativistic fairness-equity model - Tam, Nicoladie (Advances in Social Sciences Research Journal, 2014)
This study quantifies the fairness bias in relation to decision by a stimulus-response function using a relativistic fairness-equity model. The interrelationship between fairness and decision is quantified by using an Ultimatum Game (UG) experimental paradigm, in which an amount of money is shared between two parties, while the human subjects are asked to accept or reject the share. The results showed that the fairness perception is shifted upward (toward a higher positive fairness baseline in the y-intercept of the stimulus-response function) for acceptance trials, without changing the slope (which corresponds to the fairness sensitivity). On the other hand, the fairness perception is shifted downward (toward a negative fairness baseline in the y-intercept) for the rejection trials. The analysis also showed that the fairness crossover point is shifted to the left for the acceptance trials, while the fairness crossover point is shifted to the right for the rejection trials. This suggests that human subjects were more lenient to fairness when they considered slightly inequitable offers as fair in their decision to accept the offers (quantified by the fairness crossover point being shifted to the left for the acceptance trials). On the other hand, it suggests that they were greedy when they considered hyper-equitable offers as unfair (quantified by the fairness crossover point being shifted to the right for the rejection trials). The analysis also showed that there is a singularity point, in which the most equitable offer (even-split) is always considered as the fairest, even when they rejected the offers. This absolute equity is rated as the fairest (even fairer than any of the hyper-equitable offers) independent of whether the subjects decided to accept or reject the offers. These results suggested that when human subjects decided to accept or reject the offer, they included both self-regarding and other-regarding concerns, by using both self-centered and other-centered frames of reference in assessing fairness. The inclusiveness of both parties in the fairness consideration provides an optimal solution to maximize the gains for both parties at the most equitable offer (even-split) without creating conflict-of-interest. The changes in fairness perception are quantified by the shifting of the stimulus-response curve up/down (changing the fairness baseline) or left/right (changing the fairness leniency), without changing the slope (the fairness sensitivity), when the decision is made to accept or reject the offers.